The Apple Dumpling Gang [videorecording (DVD)] - Tokar, Norman, 1920-1979; Bixby, Bill, 1934-1993; Clark, Susan, 1940-; Knotts, Don, 1924-2006; Conway, Tim; Morgan, Harry, 1915-2011; Wayne, David, 1914-1995; Adrian, Iris, 1912-1994 (Buena Vista Home Entertainment, 2003)
A roving bachelor inherits three young orphans and a wealth of problems. When the kids discover a gold nugget they must fend off the greedy townspeople, so they join forces with bumbling outlaws to stage a robbery of the gold.